2007
DOI: 10.1177/1742715007073074
|View full text |Cite
|
Sign up to set email alerts
|

Existentialism and Leadership: A Response to John Lawler with Some Further Thoughts

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…Philosophy provides a framework within which we interpret our experiences and judge ourselves and situations' (Rice, 1960: 135). Since then, a number of authors have suggested philosophy can enhance organization studies and management education (Ashman, 2007;Calori, 2003;Chatterjee, 1998;Chia and Morgan, 1996;Cooper and Burrell, 1988;Gosling, 1996;Grint, 2007;Hendry, 2006;Martin, 2006). It is this work I wish to contribute to, by offering a way of thinking aboutand teaching-leadership through a philosophical lens.…”
Section: Towards a Rejection Of Essentialist Approaches To Leadershipmentioning
confidence: 99%
“…Philosophy provides a framework within which we interpret our experiences and judge ourselves and situations' (Rice, 1960: 135). Since then, a number of authors have suggested philosophy can enhance organization studies and management education (Ashman, 2007;Calori, 2003;Chatterjee, 1998;Chia and Morgan, 1996;Cooper and Burrell, 1988;Gosling, 1996;Grint, 2007;Hendry, 2006;Martin, 2006). It is this work I wish to contribute to, by offering a way of thinking aboutand teaching-leadership through a philosophical lens.…”
Section: Towards a Rejection Of Essentialist Approaches To Leadershipmentioning
confidence: 99%
“…They argue that the existential perspective can deepen the understanding of leadership as it values the individual and the subjective, and acknowledges the inter-subjective dynamics of relationships in leadership. Ashman (2007) suggests that existentialism contributes to the study of leadership by focusing the attention on the everyday experiences of subjects, rather than on the abstract generalizations common to leadership research. Existentialism is increasingly utilized within organization studies and has been argued to be particularly useful in integrating the individual and organizational levels of analysis (Pauchant & Morin, 2008).…”
Section: The Contribution Of Existentialism To Organization Studiesmentioning
confidence: 99%
“…We suggest that executives who persist in maintaining the outdated shareholder value myth (Stout, 2012) are engaging in a denial perhaps best described as a kind of existential "bad faith" (Sartre, 1993;Ashman, 2007). For too long, many business leaders have indulged in a similar kind of bad faith emblematic of their own denial that their companies have moral obligations for their impact (including unintentional) on society.…”
Section: A Crisis Of Purposementioning
confidence: 96%